Contours of value capture : India's neoliberal path of industrial development - Roy, Satyaki (Cambridge : Cambridge University Press, 2020)
This book provides a critical perspective on contemporary debates on industrialisation in India. It aims to study the process of industrialisation at a conceptual level and articulate and contest the evolving debates and discourses. Instituting a market led growth in India ended in a trajectory that depends heavily on profit income led and corporate driven growth. However, the performances as well as fault lines assessed in terms of industrial growth are often restricted to a discourse on shifting relative importance of agriculture, industry and services and are largely pegged on the state versus private debate. It appears that the heterogeneous space of critical perspective tends to undermine the more fundamental questions that need to be raised in relation to the larger perspective of capitalist industrialisation in India. This book addresses these questions and provides insights into the complexities of the process and growth of industrialisation as it has played out in contemporary India.
Manufacturing versus services: a misplaced debate -- Global production network: India and developing countries -- Financialisation in India: emerging trends in the corporate sector -- Hierarchies of capital and the architecture of value capture -- Informality: regime of accumulation and discourse of power -- Self-employment as disguised dispossession -- Land acquisition in India: revisiting primitive accumulation -- Decoding resistance and class formation in the neoliberal regime.
Title from publisher's bibliographic system (viewed on 02 Apr 2020).
Keywords: Industrialization -- India; Manufacturing industries -- India; Service industries -- India; India -- Economic policy